Pengaruh Motivasi Kerja Terhadap Kinerja Karyawan di Perusahaan Jasa Event CV. Kopi Panas Production Bali - Putu Surya Laksana Rahjasa (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Pariwisata Bali, 2022)
This research aims to analyze the effect of work motivation on employee performance at service companies' event CV. Kopi Panas Production Bali. The research used a sampling technique saturated to give equal opportunity to each population selected to be a member of the sample, that is 15 respondents who are an employee of CV. Kopi Panas Production Bali. The data were collected using a questionnaire, with validity test, reliability, simple linear regression, coefficient of determination analysis, and t-test with the help of SPSS program version 23. Then obtained the results show that the test device used is valid and reliable, the analysis results show the influence of a strong relationship and positive, and the result analysis shows a strong and positive relationship and significance between employee work motivation to employee performance equal to 74,4%.